Genetic variation of the hair coat properties and the milk yield of Holstein cows managed under shade in a tropical environment - Maia, Alex Sandro Campos; Silva, Roberto Gomes da; Bertipaglia, Elaine Cristina Abaker; Muñoz, Mario Cerón (Brazilian Journal of Veterinary Research and Animal Science, 2005)
Present study is aimed at an evaluation of the genetic and environmental effects of the coat colour and physical characteristics on the first lactation yield in Holstein cows managed under shade. Data from 449 cows were analyzed by the least-squares method and Restricted Maximum Likelihood (REML) was used to estimate (co)variance components under the Animal Model. The results showed that predominantly white Holstein cows tended to present higher milk yield than those predominantly black, when managed in large stalls with fans and sprinklers in a tropical environment. The physical characteristics have negative association with milk yield, except for the hair diameter. This association favours the heat transfer through the coat and is widely favourable in hot environments. High heritability estimates together with the high genetic correlations of milk yield and the hair properties is an evidence of the possibility of a selection for increased milk yield together with the selection towards a less dense coat with thick, short, settled hairs.